Comparing the concept of self in FAP, ACT, and in Skinner’s work (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Several behavioral analysts have extensively debated about the self, including B. F. Skinner and the proponents of the Functional Analytic Psychotherapy (FAP) and Acceptance and Commitment Therapy (ACT). Despite the current relevance of these two psychotherapies, their discussions regarding the self lacks integration. This paper aims to present a brief assessment of the similarities and differences regarding the concept of self in Skinner’s work, FAP and ACT literature. To do so, this paper reviews the construction process of the concept of self, starting from preliminary formulations in Skinner’s work and working its way through FAP’s and ACT’s texts. Stemming from these definitions, interaction patterns between the individual and the environment are described in terms of functional relations and basic behavioral principles,resulting in three functional diagnostic categories that exemplifies the psychological issues most reported in clinical practice.
Keywords: self; clinical behavior analysis; third wave psychotherapies; functional analytic psychotherapy; acceptance and commitment therapy